Pocket resolution in regenerative treatment of intrabony defects with papilla preservation techniques: A systematic review and meta‐analysis of randomized clinical trials. (5th April 2021) - Aimetti, Mario; Fratini, Adriano; Manavella, Valeria; Giraudi, Marta; Citterio, Filippo; Ferrarotti, Francesco; Mariani, Giulia Maria; Cairo, Francesco; Baima, Giacomo; Romano, Federica
Abstract: Aim: To systematically assess the clinical performance of different approaches for periodontal regeneration of intrabony defects in terms of pocket resolution compared to access surgery with papilla preservation techniques (PPTs). Material and Methods: Systematic literature searches were conducted on PubMed, EMBASE, and CENTRAL up to April 2020 to identify RCTs on regenerative treatment [guided tissue regeneration (GTR) or enamel matrix derivative (EMD) with or without biomaterials] of intrabony defects using PPTs. Results were expressed as weighted mean percentages (WMP) or risk ratios of pocket resolution at 12 months (considering both final PD ≤ 3 mm and ≤4 mm). Results: A total of 12 RCTs were included. Based on a final PD ≤ 3 mm or PD ≤ 4 mm, the WMP of pocket resolution was 61.4% and 92.1%, respectively. EMD and GTR obtained comparable results. Pairwise meta‐analysis identified a greater probability of achieving pocket resolution for GTR compared to PPTs. The number needed to treat for GTR to obtain one extra intrabony defect achieving PD ≤ 3 mm or PD ≤ 4 mm over PPTs was 2 and 4, respectively. Conclusion: Regenerative surgery represents a viable approach to obtain final PD ≤ 4 mm in the short‐term.